Planning Process in the Contenxt of Cooperative Federalism A report by Group of Members of the Planning Commission - Planning Commission (Planning Commission, 1996)
The report discusses the complexities of development planning in India, emphasizing the need for a clear distinction between plan and non-plan expenditures. It highlights the challenges faced by special category states and the importance of maintaining discipline in plan expenditures to ensure effective resource allocation. The document advocates for a cooperative federalism approach, where states have greater autonomy in formulating their plans while still aligning with national goals. It suggests reforms in the planning process, including the phasing out of Centrally Sponsored Schemes and a shift towards a more decentralized and participative planning framework. The role of the Planning Commission is underscored as essential in creating a macroeconomic environment conducive to development.
Government of India Planning Commission New Delhi
Government of India Planning Commission New Delhi
Keywords: Plan Expenditure; Non-Plan Expenditure; Special Category States; Cooperative Federalism; Planning Commission; Resource Allocation; Development Planning; Basic Minimum Services; Economic Disparities; Decentralized Planning